Review on blade propulsive efficiency - Kleshnev, V. (BioRow, 2019)
Blade efficiency is very popular topic in rowing community discussions, and opinions are still quite controversial. The most "old-fashioned" idea is that long oar angles at the catch make the blade work inefficient, because "the oar pushes the pin inwards instead of moving boat forward". This myth is quite easy to disprove with understanding of a very simple fact: power is the scalar product of the force and velocity vectors (magnitudes multiplied by the cosine of the angle between them), so when these two vectors are perpendicular one to another (cosine 90o = 0), the power production equates zero. As the sideways force at the blade/pin is perpendicular to the boat velocity, it does not produce any waste power by itself (RBN 2006/06). Longer catch angles only make the oar dynamic gearing heavier (similar to riding a bike on high gears), but it do not create energy losses by itself nor does it decrease the blade efficiency.